Buforin II-Escherichia coli's DNA interactome: Routes to elucidate the molecular mechanisms of its antimicrobial activity (2021)
The increase of multi-resistant bacteria in the last decade has become a global health issue that requires the development of alternative treatments. Antimicrobial peptides are of great interest due to their high effectiveness and differential mechanisms.Buforin II (BUFII) is a 21 amino acid antibacterial peptide that is thought to kill bacteria by entering across the membrane and interacting with intracellular molecules that are possibly involved in vital mechanisms. However, these specific interactions are still unknown, and thus far no reports are available in targeted regions or DNA sequences associated with bacterial death. Here, we proposed a study of the interaction between BUFII and the DNA of Escherichia coli using molecular, spectroscopic and microscopic techniques, complemented with whole genome sequencing. We developed an in vitro method to identify the Escherichia coli DNA interactome with BUFII using the BUFII-magnetite nanobioconjugates. This approach allows taking advantage of the strong magnetic response of the conjugates to isolate the interacting moieties. The complete biophysical study conducted here allowed us to put forward the notion that BUFII interacts with DNA very strongly most likely due to electrostatic interactions. As a result, the BUFII-DNA pair can form spherical supramolecular complexes with nanoscale dimensions where DNA is likely supercoiled. The pull-down approach introduced here along with the complementary biophysical techniques might be helpful to improve the rational peptide design and discovery by providing a more robust set of recommendations regarding the targeted interactions with bacterial components responsible for resistance.